Adomian decomposition method for solving nonlinear fractional sturm-liouville problem - Ercan, Ahu (My University, 2020)
In the present paper, the Adomian decomposition method is employed for solving nonlinear fractional Sturm-Liouville equation. The numerical results for the eigenfunctions and the eigenvalues are obtained. Also, the present results are demonstrated by the tables and the graphs for different values of considered problem.
Keywords: Matematik